editorial board - Srinakharinwirot Research and Development Journal of Humanities and Social Sciences (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2024)
Srinakharinwirot Research and Development Journal of Humanities and Social Sciences